2017
DOI: 10.1186/s40663-017-0116-9
|View full text |Cite
|
Sign up to set email alerts
|

Fujian cypress and two other threatened tree species in three conservation zones of a nature reserve in north-western Vietnam

Abstract: Background: Fujian cypress (Fokienia hodginsii) is a highly valued but endangered tree species. The Ta Xua Nature Reserve in Vietnam is one of its main conservation centers. This nature reserve consists of a fully protected core zone, a buffer zone in which low intensity forest use is permitted, and a forest restoration zone in which forest regenerates after shifting cultivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The ecology protection red line is an important innovation in Chinese ecological construction. China is the first country in the world to apply the ecology protection red line theory to national ecological management [11]. The ecology protection red line is similar to the protected area system, national park system, and natural reserve network [12].…”
Section: Introductionmentioning
confidence: 99%
“…The ecology protection red line is an important innovation in Chinese ecological construction. China is the first country in the world to apply the ecology protection red line theory to national ecological management [11]. The ecology protection red line is similar to the protected area system, national park system, and natural reserve network [12].…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have focused on forest regeneration in both of these forest types. Dao and Hölscher [ 44 ] examined the regeneration status of three threatened species in north-western Vietnam and found that most of those tree species regenerated in core zones, while their regeneration was poorer in buffer zones and restoration zones. Van and Cochard [ 45 ] suggested that forest isolation contributed to decreasing regeneration of rare tree species in lowland hillside rainforests in central Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have focused on forest regeneration in these forests. Dao and Hölscher [43] examined the regeneration status of three threatened species in north-western Vietnam, and found that most of those tree species regenerated in core zones while their regeneration was poorer in buffer zones and restoration zones. Van and Cochard [44] suggested that forest isolation contributed to decreasing regeneration of rare tree species in lowland hillside rainforests in central Vietnam.…”
Section: Introductionmentioning
confidence: 99%